20 let Německého ústavu pro současné dějiny (Czech Journal of International Relations, 1966)
The German Institute for Contemporary History in Berlin completed twenty years of existence on March 1, 1966. It is not a long time at all, considering the fact that the institute, from its original purpose of collecting material on the history of the present, has grown through documentation and information activities into the central body of the German Democratic Republic for research on the history of the present.